Mannosylated Linear and Cyclic Single Amino Acid Mutant Peptides Using a Small 10 Amino Acid Linker Constitute Promising Candidates Against Multiple Sclerosis - Day, Stephanie; Tselios, Theodore; Androutsou, Maria-Eleni; Tapeinou, Anthi; Frilligou, Irene; Stojanovska, Lily; Matsoukas, John; Apostolopoulos, Vasso (Frontiers in Immunology, 2015)
Multiple sclerosis (MS) is a serious autoimmune demyelinating disease leading to loss of neurological function. The design and synthesis of various altered peptide ligands (APLs) of immunodominant epitopes of myelin proteins to alter the autoimmune response, is a promising therapeutic approach for MS. In this study, linear and cyclic peptide analogues based on the myelin basic protein 83-99 (MBP83-99) immunodominant epitope conjugated to reduced mannan via the (KG)5 and KLH bridge respectively, were evaluated for their biological/immunological profiles in SJL/J mice. Of all the peptide analogues tested, linear MBP83-99(F91) and linear MBP83-99(Y91) conjugated to reduced mannan via a (KG)5 linker and cyclic MBP83-99(F91) conjugated to reduce mannan via KLH linker, yielded the best immunological profile and constitute novel candidates for further immunotherapeutic studies against MS in animal models and in human clinical trials.